Systematics of the New Caledonian endemic genus Taophila Heller (Coleoptera: Chrysomelidae, Eumolpinae) combining morphological, molecular and ecological data, with description of two new species. (7th October 2013) - GÓMEZ‐ZURITA, JESÚS; CARDOSO, ANABELA
Abstract The genus Taophila Heller, 1916 was considered a monotypic taxon until the recent addition of 11 new species. We examined the recent revision of this genus to evaluate these new taxonomic considerations in the light of molecular data for a sample of 85 individuals in 8 out of 12 Taophila species, and to provide characters for a phylogenetic systematic analysis of the genus. These data include two mitochondrial DNA markers (cox1 and rrnS) and one nuclear DNA marker (wingless) to infer the species phylogeny, and one gene from the chloroplastic DNA (psbA‐trnH) of putatively ingested plant tissue for diet inference. Molecular data support the monophyly of the species studied, except for T. subsericea Heller, 1916, which possibly represents an ancient genetic polymorphism. The molecular phylogeny and a reassessment of morphological characters are used to propose several taxonomic changes that will achieve stable systematics in Taophila, including: (i) description of two new species, T. aphroditasp.n. and T. gaeasp.n., both related to T. mars Samuelson, 2010; (ii) removal of T. cancellata Samuelson, 2010 from Taophila and its new combination with Dematochroma Baly, 1864; (iii) proposal of two new subgenera in Taophila to reflect deep phylogenetic divergence and profound morphological discrepancies with the anatomy of the generic type and relatives, Jolivetianasubgen.n. (type: Taophila mantillerii Jolivet, Verma & Mille, 2007) and Lapitasubgen.n. (type: Taophila mars Samuelson, 2010). The analysis of putative diet sequences retrieved from all the species available for analysis show widespread associations with ferns and legumes, which can be traced back to the hypothetical common ancestor of Taophila, and an apparent generalist diet for the species in Lapitasubgen.n. This published work has been register in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:05F9C680‐3325‐409E‐A881‐C8A5AE1D136F.